The Role of Parents in Character Education for Children: A Narrative Analysis by A.J. Greimas on the Youtube Channel Bestie Life-Ḥayātun afḍal - Emil Nurdiani; R. Edi Komaruddin; Yadi Mardiansyah (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
The YouTube channel Bestie Life – Ḥayātun Afḍal features inspirational stories that highlight the role of parents in guiding their children. This research aims to analyze the role of parents in character education for children through a review of actantial structure based on A.J. Greimas's narrative theory. The research method used is library research with a descriptive approach, focusing on the analysis of narrative texts. The data source for this research is a collection of stories from the Bestie Life – Ḥayātun Afḍal channel, namely